Clinical proteomics in neurodegenerative disease - Jahn, Holger (Henry Stewart Talks, 2013)
Neurodegenerative disease, Dementia, Alzheimer´s, Clinical use of proteomic methods for diagnosis and biomarker development, An example: CE-MS in Alzheimer research, Scope, limits, pitfalls, prospects